Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/codi.13727
|View full text |Cite
|
Sign up to set email alerts
|

The PTPN13 Y2081D (T>G) (rs989902) polymorphism is associated with an increased risk of sporadic colorectal cancer

Abstract: PTPN13 rs989902 is significantly associated with the risk of CRC in the Polish population. Given that this report provides the first evidence of an association of PTPN13 rs989902 with the risk of CRC in a Caucasian population, further large scale studies are necessary to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is also involved in the inhibition of Fas‐induced apoptosis. Laczmanska et al () identified an association of PTPN13 rs989902 with the risk of sporadic colorectal cancer in a Caucasian population. Adipose tissue plays critical roles in the regulation of energy homeostasis, as a reservoir, by storing and releasing fuel, and as an endocrine organ, by secreting a number of hormones and cytokines (Spiegelman & Flier, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is also involved in the inhibition of Fas‐induced apoptosis. Laczmanska et al () identified an association of PTPN13 rs989902 with the risk of sporadic colorectal cancer in a Caucasian population. Adipose tissue plays critical roles in the regulation of energy homeostasis, as a reservoir, by storing and releasing fuel, and as an endocrine organ, by secreting a number of hormones and cytokines (Spiegelman & Flier, ).…”
Section: Resultsmentioning
confidence: 99%
“…We found no correlation between PTPN13 and its regulator miR-200c . In addition to post-transcriptional regulation of PTPN13 in CRC by miRNAs [ 41 , 42 ], its expression might be regulated through promoter hypermethylation or loss of heterozygosity [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides LOH, other genetic variations may be relevant to the residual allele, particularly SNPs [136]. The Y2081D Tyr2081Asp (T > G), rs989902 (rs for SNP reference), in exon 39, near the PTPN13 phosphatase domain [137], is associated with colorectal cancer in Polish patients (relative risk compared to the "wild-type" genotype: 2.087) [138], and with HNSCC in American patients (Odds Ratio, OR, =1.26) [139]. A meta-analysis of data from Caucasian and Asian patients confirmed its association with HNSCC (OR = 1.23), but a protective role was attributed to PTPN13 in colorectal cancer (OR = 0.51).…”
Section: Single Nucleotide Polymorphisms (Snp)mentioning
confidence: 99%